Optimization of Management of Islamic Philanthropy Based on Productive Ownership Efforts for Empowering the Economic Independence - M. Zidny Nafi' Hasbi; Ipuk Widayanti (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
Islamic philanthropy is a practice of generosity in the Islamic tradition through zakat, infaq, alms, and waqf (ZISWAF). In Islamic history, the practice of waqf has had a socio-economic impact on society. Waqf is one of the Islamic financial instruments that have the potential as an instrument for developing the national economy. Modern Islamic Boarding School Darussalam Gontor waqf institute has the highest structure in determining policy and economic development, namely the waqf institution. Among the boarding school that can be considered successful in managing productive waqf is Boarding School Darussalam Gontor. The purpose of this study is to analyze productive waqf managed by PMDG. The research method uses a qualitative descriptive approach. Data collection techniques include observation, documentation, and deep interviews. Data analysis uses Miles and Huberman's model theory. The findings of this study state that the collected waqf funds are managed properly and professionally so that the distribution of productive waqf can be carried out in a dialogical manner for the development of several business fields in PMDG. The implementation of productive waqf has long-term implications for PMDG, especially in the field of education and teaching. The growing facilities can have a big impact on improving the quality of education which is getting better. Productive waqf funds also contribute to the economy of the surrounding community. It is hoped that the productive waqf management model carried out by PMDG can be a reference for practitioners in managing productive waqf.